Heat and thermodynamics : an intermediate textbook - Zemansky, Mark Waldo; Dittman, Richard H. (New York : McGraw-Hill;1997, 1997)
This book is divided into two parts: Fundamental Concepts; and Applications of fundamental concepts of Heat and Thermodynamics.
Keywords: Thermodynamics; Heat; Heat; Thermodynamics